Intersectional Pandemics in Bangladesh: The Effects of COVID-19 on Girls. Issue 3 (1st December 2020) - Siddiqa, Nasrin
Abstract : Girls and women are the first victims of any calamity, pandemic, or disaster in developing countries like Bangladesh. As it is, they are very often denied health care, are forced to endure child marriage and early motherhood, and are frequently subjected to violence. Given this unprecedented COVID-19 pandemic they are now suffering immensely. COVID-19 threatens girls' rights in countries around the world and will have far-reaching impacts on their health and wellbeing, education, and protection. Self-isolation has increased the rates of gender-based violence. Early marriage and pregnancy are among the drastic effects of school closures and many parents have married off their underage daughters or sold them off to rich families as domestic workers to reduce their economic burden.